2016
DOI: 10.1111/sms.12697
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exercise in normal and hot ambient conditions on the pharmacokinetics of inhaled terbutaline in trained men

Abstract: This study investigated the pharmacokinetics of inhaled terbutaline at rest and after exercise in normal and hot ambient conditions with respect to doping analysis. Thirteen trained young men participated in the study. Urine and blood samples were collected after inhalation of 4 mg terbutaline during three trials: exercise in hot ambient conditions (30-35 °C) (EXH), exercise in normal ambient conditions (20-25 °C) (EX), and rest (20-25 °C) (R). Exercise consisted of 130 min at various intensities. Adjustment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Median levels following the 200 µg dose at 2 h were 1.0 and 1.1 ng/mL for (R)‐salmeterol and (S)‐salmeterol, respectively, and median enantiomers levels at 24 h were 0.21 and 0.25 ng/mL for (R)‐ and (S)‐salmeterol, respectively. These urine levels were not controlled for dilution effects, and the variation was in line with previous studies which have identified hydration and other factors as determinants of urine levels of beta2‐agonists …”
Section: Resultssupporting
confidence: 87%
“…Median levels following the 200 µg dose at 2 h were 1.0 and 1.1 ng/mL for (R)‐salmeterol and (S)‐salmeterol, respectively, and median enantiomers levels at 24 h were 0.21 and 0.25 ng/mL for (R)‐ and (S)‐salmeterol, respectively. These urine levels were not controlled for dilution effects, and the variation was in line with previous studies which have identified hydration and other factors as determinants of urine levels of beta2‐agonists …”
Section: Resultssupporting
confidence: 87%
“…; Kreiberg et al . ). Such concentrations are equivalent or even higher than those observed after oral administration of 10 mg terbutaline (Elers et al .…”
Section: Methodsmentioning
confidence: 97%
“…The outcome was that after 130 minutes of cycling, urinary concentrations of terbutaline were significantly higher than after resting and this difference remained statistically significant, even when correction for urinary SG was applied. 29 Thus there is sound evidence that exercise increases the urinary excretion both salbutamol and terbutaline.…”
Section: Exercise Increases Urinary Concentrations Of Beta-2 Agonistsmentioning
confidence: 99%